Ethical Issues in Uncontrolled Donation After Circulatory Determination of Death: A Scoping Review to Reveal Areas of Broad Consensus, and Those for Future Research - Anastasia Georgiou; Weiyi Tan; Mihnea I. Ionescu; Isla L. Kuhn; Zoe Fritz (Transplant International)
Uncontrolled donation after circulatory determination of death (uDCD) protocols are established in several countries with good outcomes. We reviewed the literature between 1997 and 2024 to identify ethical issues. 33 papers were identified. Several areas of continued ethical debate were delineated: the role of advanced life support techniques; the ethical acceptability of aortic occlusion balloons; the nature and timing of consent to organ preserving techniques; whether best interests can/should extend beyond individual bodily integrity in this context. Further empirical research and ethical analyses are needed in these domains. Broad consensus was identified on several issues including: decisions about termination of resuscitation and entry into a uDCD protocol should be made by different teams; at least 20–30 min of cardio-pulmonary resuscitation is required; a hands-off period of 5–7 min is required alongside continuous monitoring; organ preserving techniques should be as minimally invasive as possible; families should be approached early to discuss organ donation by trained staff; public knowledge and engagement about uDCD is poor and must be improved; transparency and informed consent are essential for potential uDCD organ recipients. To maintain transparency and encourage positive public engagement we propose a name change from uDCD to Organ Donation after Sudden Irreversible Cardiac Arrest (ODASICA).